Analyzing dynamic change of tourism destination image under the occurrence of a natural disaster: evidence from Japan. Issue 16 (17th August 2020) - Wu, Lingling; Shimizu, Tetsuo
ABSTRACT: This study attempts to investigate the dynamic impact of a natural disaster on tourism destination image. The data analysis through a case study of Japan confirmed three hypotheses. Firstly, the results showed that a natural disaster would bring a significant damage to tourism destination image, but the negative impact reduced over time. Secondly, it confirmed that the change of destination image after a natural disaster was different for tourists with different country of origin. Lastly, this study also revealed that the influences of destination image on travel intention would change under the occurrence of a natural disaster. Based on these results, some implications have been derived for tourism destinations to develop image restoration and tourism recovery strategies in the future.